Modelo experimental de disfunção temporomandibular em ratos - Gomes, Kátia do Nascimento (2005)
Studies on rats spontaneous behaviors and pharmacological effects of drugs on them, as well as their body weight and histopathological analysis of their joints were carried out to investigate the effect of chronic inflammation of the temporomandibular articulation induced by the administration of Complete Freund Adjuvant (CFA) compared with the acute and subacute stimulus of 2.5% formalin. After CFA, 2.5% formalin and 0.9% saline injection, the animals were daily observed during 30 minutes for 7 days; thereafter, they were killed for removal of the articular and periarticular region for evaluation of inflammatory changes induced by CFA and formalin compared with control rats. The main behavioral changes induced by CFA concerned chewing-like, rest/sleeping, freezing, grooming or rubbing whereas those induced by formalin were grooming and scratching. The CFA-induced behavioral changes were time-dependent from the 2nd up to the 7th day, while the formalin-induced changes occurred in the 1st day only. For pharmacological testing, morphine (4 mg/kg), indomethacin (5 mg/kg) and lidocaine with phenilephrine were used. In the CFA rats, morphine reduced significantly chewing-like and grooming, indomethacin decreased grooming and increased sleeping. Freezing was not changed by any drugs. In the formalin rats, grooming and scratching towards the orofacial region were increased and those behaviors were significantly decreased by morphine and formalin. The effects of the drugs on the different behaviors shown above show their nociceptive meaning. Moreover, the body weight of the animals was not changed. In both CFA and formalin groups, the histological analysis evidenced degenerative and small periarticular inflammatory infiltration. Neuroplasticity changes may be related to the CFA induction and the nociceptive meaning of the behaviors may be useful for experimental therapeutic studies.